High-resistivity magnetic powder, preparation method thereof and magnet

By setting up phosphorus and zinc oxide coatings on samarium iron nitrogen and ferrite magnetic powder, and through ball milling technology, the resistivity of the permanent magnet is improved, and the balance problem of permanent magnets between high resistivity and low cost is solved. Reduces eddy current loss and improves temperature resistance.

CN119230234APending Publication Date: 2024-12-31HENGDIAN GRP DMEGC MAGNETICS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310783581.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing permanent magnets are difficult to balance between high resistivity and low cost, resulting in eddy current loss and temperature performance problems, affecting the efficiency and life of the motor.

Method used

The samarium-iron-nitrogen composite magnetic powder and ferrite composite magnetic powder are used to improve the resistivity of the magnetic powder by setting up a phosphorus and zinc oxide coating layer, and uniform mixing and insulation of the magnetic powder are achieved through ball milling technology to reduce costs.

Benefits of technology

It significantly reduces eddy current loss, improves the temperature resistance of magnets, and reduces production costs, and has higher economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004311522980000121
    Figure BDA0004311522980000121
  • Figure BDA0004311522980000131
    Figure BDA0004311522980000131
Patent Text Reader

Abstract

The invention provides high-resistivity magnetic powder, a preparation method thereof and a magnet. The high-resistivity magnetic powder comprises samarium-iron-nitrogen composite magnetic powder and ferrite composite magnetic powder; the samarium-iron-nitrogen composite magnetic powder comprises a samarium-iron-nitrogen inner core, and a phosphorus coating layer and a zinc oxide coating layer which are sequentially arranged on the surface of the samarium-iron-nitrogen inner core from inside to outside; the ferrite composite magnetic powder comprises a ferrite core and a zinc oxide coating layer arranged on the surface of the ferrite core. By arranging the special coating layer and the specific magnetic powder combination, the resistivity of the magnetic powder can be improved, so that the eddy-current loss of a corresponding magnet can be reduced, and the temperature resistance of the magnet is improved. Meanwhile, a ferrite material with lower price is adopted, so that the cost can be reduced, and higher economic benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic materials, and relates to a rare earth permanent magnetic material, in particular to a high-resistivity magnetic powder and a preparation method thereof, and a magnet. Background Art

[0002] When permanent magnets are used in motors, when the coils in the motors are energized, the permanent magnets will generate eddy currents, causing the temperature to rise and the performance to decline, which will lead to a decrease in the output power and efficiency of the motor. In the worst case, the magnets will be broken down by high voltage and cause the motor to fail. The temperature rise caused by eddy current loss in the rotor directly affects the service life and reliability of the motor. Increasing the resistivity of the magnets can effectively reduce the eddy current loss generated by the magnets, thereby avoiding the above problems.

[0003] In the application of permanent magnet motors, the commonly used permanent magnets are sintered NdFeB, bonded NdFeB and sintered ferrite. Sintered NdFeB permanent magnet material adopts powder metallurgy process. The smelted alloy is made into powder and pressed into pressed embryos in a magnetic field. The pressed embryos are sintered in an inert gas or vacuum to achieve densification. In order to improve the coercive force of the magnet, aging heat treatment is usually required.

[0004] Bonded NdFeB is a synthetic magnet; bonded NdFeB magnets are made by mixing NdFeB magnetic powder and a binder through "pressing molding" or "injection molding". Bonded magnets have high dimensional accuracy and can be made into relatively complex magnetic components, and have the characteristics of one-time molding and multi-pole orientation; bonded NdFeB has high mechanical strength and can be molded at the same time with other supporting components during molding.

[0005] Sintered ferrite is low-cost and has excellent corrosion resistance and high temperature resistance, with a maximum operating temperature of 250°C. Its magnetic properties are lower than those of sintered NdFeB magnets, but sintered ferrite is still widely used.

[0006] However, it is difficult for the above three permanent magnets to strike a balance between high resistivity and low cost. Among them, sintered NdFeB has the highest performance, but its resistivity is only 10 -4 Ω·cm level, and the price of sintered NdFeB is also the most expensive; the performance of bonded NdFeB is lower than that of sintered NdFeB, and the resistivity is lower; although sintered ferrite has low cost, its resistivity is low and is not enough for high-performance motors.

[0007] Therefore, there is an urgent need for a magnetic material that has a higher resistivity, can reduce eddy current losses, and has a lower cost. Summary of the invention

[0008] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high-resistivity magnetic powder and a preparation method thereof and a magnet. The high-resistivity magnetic powder of the present invention includes samarium iron nitrogen composite magnetic powder and ferrite composite magnetic powder. By setting a special coating layer and a specific magnetic powder combination, the resistivity of the magnetic powder can be improved, thereby reducing the eddy current loss of the corresponding magnet and improving the temperature resistance of the magnet. At the same time, the present invention uses a relatively low-priced ferrite material, which can reduce costs and has higher economic benefits.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a high resistivity magnetic powder, the high resistivity magnetic powder comprising samarium iron nitrogen composite magnetic powder and ferrite composite magnetic powder;

[0011] The samarium iron nitrogen composite magnetic powder comprises a samarium iron nitrogen core, and a phosphorus coating layer and a zinc oxide coating layer sequentially arranged on the surface of the samarium iron nitrogen core from the inside to the outside;

[0012] The ferrite composite magnetic powder comprises a ferrite core and a zinc oxide coating layer arranged on the surface of the ferrite core.

[0013] In the present invention, the "high resistivity" refers to a resistivity of 1.0×10 -2 Ω·cm or more, more preferably 1 Ω·cm or more.

[0014] The present invention provides a high resistivity magnetic powder, including samarium iron nitrogen composite magnetic powder and ferrite composite magnetic powder, wherein the surface of the samarium iron nitrogen core is coated with a phosphorus coating layer and a zinc oxide coating layer in sequence, the phosphorus coating layer can prevent the samarium iron nitrogen core from being oxidized, and the zinc oxide coating layer can further improve the anti-oxidation ability of the samarium iron nitrogen material and improve the resistivity of the samarium iron nitrogen material; the surface of the ferrite core is coated with a zinc oxide coating layer, and the zinc oxide coating layer can improve the anti-oxidation ability of the ferrite material and improve the resistivity of the ferrite material; at the same time, there is a coating layer interval between the samarium iron nitrogen composite magnetic powder and the ferrite composite magnetic powder for insulation, which further improves the resistivity of the overall magnetic powder; therefore, the magnetic powder of the present invention has a high resistivity, thereby reducing the eddy current loss of the corresponding magnet and improving the temperature resistance of the magnet. In addition, the present invention uses a relatively low-priced ferrite material, which can reduce costs and has higher economic benefits.

[0015] The present invention does not specifically limit the chemical composition of the ferrite core, including but not limited to strontium ferrite and barium ferrite, and the model is further optimized according to the specific magnetic properties.

[0016] Preferably, the mass ratio of the samarium iron nitrogen composite magnetic powder to the ferrite composite magnetic powder is 100:(1-49), for example, it can be 100:1, 100:2, 100:5, 100:10, 100:15, 100:20, 100:25, 100:30, 100:40, 100:45 or 100:49, etc.

[0017] Preferably, in the samarium iron nitrogen composite magnetic powder, the thickness of the phosphorus coating layer is 10-100 nm, for example, it can be 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm or 90 nm.

[0018] Preferably, the ferrite core comprises a permanent ferrite core.

[0019] Preferably, in the samarium-iron-nitrogen composite magnetic powder, the thickness of the zinc oxide coating layer is 50-200 nm, for example, 50 nm, 70 nm, 100 nm, 150 nm, 170 nm or 200 nm.

[0020] Preferably, in the ferrite composite magnetic powder, the thickness of the zinc oxide coating layer is 50-200 nm, for example, 50 nm, 70 nm, 100 nm, 150 nm, 170 nm or 200 nm.

[0021] In a second aspect, the present invention provides a method for preparing the high resistivity magnetic powder according to the first aspect, the preparation method comprising:

[0022] Phosphorus-containing substances, ferrite magnetic powder and zinc oxide are sequentially added to the samarium iron nitrogen magnetic powder, and ball milling is performed to obtain the high resistivity magnetic powder.

[0023] The invention provides a method for preparing high resistivity magnetic powder, which has a simple process and is easy to realize in mass production. Phosphorus-containing substances can react with samarium iron nitrogen magnetic powder to form a phosphide film on its surface to prevent oxidation.

[0024] Preferably, the phosphorus-containing substance comprises phosphoric acid and / or phosphate.

[0025] Preferably, the mass ratio of the samarium iron nitrogen magnetic powder to the phosphorus-containing substance is 100:(0.1-10), for example, it can be 100:0.1, 100:0.2, 100:0.5, 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9 or 100:10, etc.

[0026] Preferably, the ferrite powder includes permanent ferrite powder.

[0027] Preferably, the mass ratio of the samarium iron nitrogen magnetic powder to the ferrite magnetic powder is 100:(1-49), for example, it can be 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9, 100:10, 100:20, 100:25, 100:30, 100:35, 100:40, 100:45 or 100:49, etc.

[0028] Preferably, the D50 particle size of the zinc oxide is 20-100 nm, for example, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm or 90 nm.

[0029] In the present invention, the zinc oxide powder has a relatively small particle size, generally at the nanometer level, and can be filled in the gaps of the magnetic powder to form a coating layer, thereby further improving the anti-oxidation ability and resistivity of the magnetic powder.

[0030] Preferably, the mass ratio of the samarium iron nitrogen magnetic powder to the zinc oxide is 100:(0.1-10), for example, it can be 100:0.1, 100:0.2, 100:0.5, 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9 or 100:10, etc.

[0031] Preferably, the ball milling is wet ball milling. The reagents used in the wet ball milling include but are not limited to at least one of ethanol, isopropanol and gasoline.

[0032] Preferably, the ball milling specifically comprises:

[0033] (1) adding a phosphorus-containing substance to the samarium iron nitrogen magnetic powder and performing a ball milling to obtain a primary ball milling material;

[0034] (2) adding ferrite powder to the primary ball mill material, and performing secondary ball milling to obtain secondary ball mill material;

[0035] (3) Add zinc oxide to the secondary ball mill material and perform ball milling for a third time.

[0036] Preferably, the samarium iron nitrogen magnetic powder is pre-ball-milled before the ball-milling.

[0037] Preferably, the pre-ball milling is wet ball milling. The reagents used in the wet ball milling include but are not limited to at least one of ethanol, isopropanol and gasoline.

[0038] Preferably, the rotation speeds of the pre-milling, primary milling, secondary milling and tertiary milling are independently 200-1500 r / min, for example, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 800 r / min, 1000 r / min, 1200 r / min or 1500 r / min, etc.

[0039] Preferably, the total time for the pre-milling, primary milling, secondary milling and tertiary milling is 0.1-10 h, for example, 0.1 h, 0.2 h, 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, etc.

[0040] Preferably, the pre-milling time is 0.1 to 8 h, for example, 0.1 h, 0.2 h, 0.5 h, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h or 8 h.

[0041] Preferably, the time for the first ball milling, the second ball milling and the third ball milling is independently 0.1 to 2 h, for example, it can be 0.1 h, 0.2 h, 0.3 h, 0.5 h, 0.7 h, 1 h, 1.2 h, 1.5 h, 1.7 h or 2 h.

[0042] Preferably, the preparation method further comprises: after the ball milling, sequentially performing the steps of separation and drying.

[0043] Preferably, after obtaining the separated product through the separation, the separated product is mixed with a coupling agent and the drying step is performed.

[0044] The present invention does not limit the type of coupling agent, including but not limited to at least one of a silane coupling agent, an aluminate coupling agent and a titanate coupling agent.

[0045] Preferably, the mass ratio of the samarium iron nitrogen magnetic powder to the coupling agent is 100:(0.1-5), for example, it can be 100:0.1, 100:0.2, 100:0.5, 100:1, 100:1.5, 100:2, 100:2.5, 100:3, 100:3.5, 100:4, 100:4.5 or 100:5, etc.

[0046] Preferably, the drying temperature is 50-200°C, for example, it can be 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 120°C, 150°C, 170°C or 200°C, and the drying time is 1-24h, for example, it can be 1h, 2h, 3h, 4h, 5h, 6h, 9h, 10h, 12h, 15h, 17h, 20h or 24h, etc.

[0047] As a preferred technical solution of the present invention, the preparation method specifically comprises:

[0048] (I) pre-milling the samarium iron nitrogen magnetic powder to obtain a pre-milled material, wherein the mass ratio of the ball milling balls used in the pre-milling to the samarium iron nitrogen magnetic powder is (5-10):1, for example, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1, etc., and the reagent used in the pre-milling includes at least one of ethanol, isopropanol and gasoline, and the mass ratio of the reagent to the samarium iron nitrogen magnetic powder is (1-2):1, for example, 1:1, 1.5:1 or 1:2, etc.;

[0049] (II) adding a phosphorus-containing substance to the pre-milled material, performing a first ball milling to obtain a first ball milled material; adding ferrite magnetic powder to the first ball milled material, performing a second ball milling to obtain a second ball milled material; adding zinc oxide to the second ball milled material, performing a third ball milling to obtain a third ball milled material;

[0050] (III) Separating the tertiary ball milling material, mixing the separated product with a coupling agent, and drying it at 50-200° C. for 1-24 h under vacuum or inert atmosphere to obtain the high resistivity magnetic powder.

[0051] In the present invention, the step of "separating the tertiary ball milling materials" includes: first separating the ball milling balls, and then performing solid-liquid separation; the solid-liquid separation method includes but is not limited to pressure filtration or suction filtration.

[0052] In a third aspect, the present invention provides a magnet comprising the high resistivity magnetic powder described in the first aspect.

[0053] Optionally, the present invention provides a method for preparing a magnet, comprising:

[0054] The dried high resistivity magnetic powder is mixed with polyamide resin for granulation at a granulation temperature of 180-230° C. to form granules, and the granules are injection molded at 210-300° C. to obtain a magnet;

[0055] The ratio of the mass of the polyamide resin to the total mass of the high resistivity magnetic powder is (5-20):100, for example, 5:100, 7:100, 9:100, 10:100, 12:100, 15:100, 17:100 or 20:100.

[0056] In the present invention, the granulation temperature may be, for example, 180°C, 190°C, 200°C, 210°C, 220°C or 230°C, etc. The injection molding temperature may be, for example, 210°C, 220°C, 230°C, 250°C, 260°C, 280°C, 290°C or 300°C, etc.

[0057] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0058] Compared with the prior art, the present invention has the following beneficial effects:

[0059] The invention provides a high-resistivity magnetic powder, comprising a samarium-iron-nitrogen composite magnetic powder and a ferrite composite magnetic powder, wherein the surface of the samarium-iron-nitrogen core is coated with a phosphorus coating layer and a zinc oxide coating layer in sequence, the phosphorus coating layer can prevent the samarium-iron-nitrogen core from being oxidized, the zinc oxide coating layer can further improve the anti-oxidation ability of the samarium-iron-nitrogen material, and can improve the resistivity of the samarium-iron-nitrogen material, and the phosphorus coating layer and the zinc oxide coating layer can fill the gap between each other, so that the overall coating is more compact; the surface of the ferrite core is coated with a zinc oxide coating layer, the zinc oxide coating layer can improve the anti-oxidation ability of the ferrite material, and can improve the resistivity of the ferrite material; at the same time, the samarium-iron-nitrogen composite magnetic powder and the ferrite composite magnetic powder can be evenly mixed by ball milling, and the coating layers are separated from each other for insulation, so as to further improve the resistivity of the overall magnetic powder; therefore, the magnetic powder of the invention has a high resistivity, thereby reducing the eddy current loss of the corresponding magnet and improving the temperature resistance of the magnet. In addition, the present invention adopts relatively low-priced ferrite materials, which can reduce costs and has higher economic benefits. DETAILED DESCRIPTION

[0060] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0061] Example 1

[0062] This embodiment provides a high resistivity magnetic powder, including samarium iron nitrogen composite magnetic powder and ferrite composite magnetic powder, wherein the mass ratio of the samarium iron nitrogen composite magnetic powder to the ferrite composite magnetic powder is 100:20;

[0063] The samarium iron nitrogen composite magnetic powder comprises a samarium iron nitrogen core, and a phosphorus coating layer and a zinc oxide coating layer sequentially arranged on the surface of the samarium iron nitrogen core from the inside to the outside, wherein the phosphorus coating layer has a thickness of 50 nm, and the zinc oxide coating layer has a thickness of 100 nm;

[0064] The ferrite composite magnetic powder comprises a ferrite core and a zinc oxide coating layer arranged on the surface of the ferrite core. The ferrite core is a permanent magnet strontium ferrite core, and the thickness of the zinc oxide coating layer is 100 nm.

[0065] This embodiment also provides a method for preparing the high resistivity magnetic powder, which specifically comprises the following steps:

[0066] 100 parts of samarium iron nitrogen magnetic powder and 150 parts of ethanol were weighed in parts by mass, and added into a ball mill for ball milling, the mass ratio of ball milling balls to samarium iron nitrogen magnetic powder was 20:1, the speed of ball milling was 1000r / min, and the total ball milling time was set to 4h; 5 parts of phosphoric acid were added after ball milling for 1h; 20 parts of ferrite magnetic powder were added after 2h; 5 parts of zinc oxide with a D50 particle size of 20nm were added after 3h. After ball milling, solid-liquid separation was performed by filter press, and 2 parts of silane coupling agent were added to the separated product for high-temperature drying under vacuum at a temperature of 100°C for 15h to obtain the high resistivity magnetic powder.

[0067] Example 2

[0068] The only difference between this embodiment and embodiment 1 is that the amount of phosphoric acid added is adjusted to 0.1 parts, so that the thickness of the phosphorus coating layer is adjusted to 10 nm.

[0069] Example 3

[0070] The only difference between this embodiment and embodiment 1 is that the amount of phosphoric acid added is adjusted to 10 parts, so that the thickness of the phosphorus coating layer is adjusted to 100 nm.

[0071] Example 4

[0072] The only difference between this embodiment and embodiment 1 is that the amount of ferrite added is adjusted to 1 part, so that the mass ratio of the samarium iron nitrogen composite magnetic powder to the ferrite composite magnetic powder is adjusted to 100:1.

[0073] Example 5

[0074] The only difference between this embodiment and embodiment 1 is that the amount of ferrite added is adjusted to 49 parts, so that the mass ratio of the samarium iron nitrogen composite magnetic powder to the ferrite composite magnetic powder is adjusted to 100:49.

[0075] Example 6

[0076] The only difference between this embodiment and embodiment 1 is that the amount of zinc oxide added is adjusted to 0.1 parts, so that the thickness of the zinc oxide coating layer in the samarium iron nitrogen composite magnetic powder is adjusted to 50 nm, and the thickness of the zinc oxide coating layer in the ferrite composite magnetic powder is adjusted to 50 nm.

[0077] Example 7

[0078] The only difference between this embodiment and embodiment 1 is that the amount of zinc oxide added is adjusted to 10 parts, so that the thickness of the zinc oxide coating layer in the samarium iron nitrogen composite magnetic powder is adjusted to 200 nm, and the thickness of the zinc oxide coating layer in the ferrite composite magnetic powder is adjusted to 200 nm.

[0079] Example 8

[0080] This embodiment provides a high resistivity magnetic powder, including samarium iron nitrogen composite magnetic powder and ferrite composite magnetic powder, wherein the mass ratio of the samarium iron nitrogen composite magnetic powder to the ferrite composite magnetic powder is 100:40;

[0081] The samarium iron nitrogen composite magnetic powder comprises a samarium iron nitrogen core, and a phosphorus coating layer and a zinc oxide coating layer sequentially arranged on the surface of the samarium iron nitrogen core from the inside to the outside, the phosphorus coating layer has a thickness of 70nm, and the zinc oxide coating layer has a thickness of 150nm;

[0082] The ferrite composite magnetic powder comprises a ferrite core and a zinc oxide coating layer arranged on the surface of the ferrite core. The ferrite core is a permanent barium ferrite core, and the thickness of the zinc oxide coating layer is 150nm.

[0083] This embodiment also provides a method for preparing the high resistivity magnetic powder, which specifically comprises the following steps:

[0084] 100 parts of samarium iron nitrogen magnetic powder and 150 parts of isopropanol were weighed in parts by mass, and added into a ball mill for ball milling, the mass ratio of ball milling balls to samarium iron nitrogen magnetic powder was 20:1, the speed of ball milling was 500r / min, and the total ball milling time was set to 10h; 7 parts of phosphoric acid were added after 2.5h of ball milling; 40 parts of ferrite were added after 5h; 7 parts of zinc oxide with a D50 particle size of 50nm were added after 7.5h. After the ball milling was completed, solid-liquid separation was performed by filter press, 4 parts of silane coupling agent were added to the separated product, and high-temperature drying was performed under vacuum at a temperature of 100°C for 15h to obtain the high resistivity magnetic powder.

[0085] Example 9

[0086] The only difference between this embodiment and embodiment 1 is that the amount of phosphoric acid added is adjusted to 0.05 parts, so that the thickness of the phosphorus coating layer is adjusted to 5 nm.

[0087] Example 10

[0088] The only difference between this embodiment and embodiment 1 is that the amount of phosphoric acid added is adjusted to 10.5 parts, so that the thickness of the phosphorus coating layer is adjusted to 100 nm.

[0089] Embodiment 11

[0090] The only difference between this embodiment and embodiment 1 is that the amount of ferrite added is adjusted to 0.5 parts, so that the mass ratio of the samarium iron nitrogen composite magnetic powder to the ferrite composite magnetic powder is adjusted to 100:0.5.

[0091] Example 12

[0092] The only difference between this embodiment and embodiment 1 is that the amount of ferrite added is adjusted to 49.5 parts, so that the mass ratio of the samarium iron nitrogen composite magnetic powder to the ferrite composite magnetic powder is adjusted to 100:49.5.

[0093] Example 13

[0094] The only difference between this embodiment and embodiment 1 is that the amount of zinc oxide added is adjusted to 0.05 parts, so that the thickness of the zinc oxide coating layer in the samarium iron nitrogen composite magnetic powder is adjusted to 30 nm, and the thickness of the zinc oxide coating layer in the ferrite composite magnetic powder is adjusted to 30 nm.

[0095] Embodiment 14

[0096] The difference between this embodiment and embodiment 1 is that the amount of zinc oxide added is adjusted to 10.5 parts, so that the thickness of the zinc oxide coating layer in the samarium iron nitrogen composite magnetic powder is adjusted to 200 nm, and the thickness of the zinc oxide coating layer in the ferrite composite magnetic powder is adjusted to 200 nm.

[0097] Comparative Example 1

[0098] The only difference between this comparative example and Example 1 is that no ferrite magnetic powder is added, that is, the prepared magnetic powder does not contain ferrite composite magnetic powder.

[0099] Comparative Example 2

[0100] The only difference between this comparative example and Example 1 is that no samarium iron nitrogen magnetic powder and phosphoric acid are added, that is, the prepared magnetic powder does not contain samarium iron nitrogen composite magnetic powder.

[0101] Comparative Example 3

[0102] The only difference between this comparative example and Example 1 is that phosphoric acid is not added, so that the surface of the samarium iron nitrogen core is only coated with a zinc oxide coating layer.

[0103] Comparative Example 4

[0104] The only difference between this comparative example and Example 1 is that zinc oxide is not added, so that there is no zinc oxide coating layer in the samarium-iron-nitrogen composite magnetic powder and the ferrite composite magnetic powder.

[0105] Comparative Example 5

[0106] The difference between this comparative example and Example 1 is that phosphoric acid, ferrite and zinc oxide are added together for ball milling during ball milling for 1 hour.

[0107] Comparative Example 6

[0108] The difference between this comparative example and Example 1 is that ferrite and zinc oxide are added together for ball milling during ball milling for 2 hours.

[0109] Application Example 1

[0110] This application example provides a method for preparing a magnet, comprising:

[0111] The magnetic powder obtained in Example 1 was mixed with 12 parts of polyamide resin (based on 100 parts of magnetic powder) for granulation at a granulation temperature of 210° C. to form granules. The granules were injection molded at 260° C. into standard samples, i.e., magnets.

[0112] Application Example 2-14

[0113] The only difference from Application Example 1 is that the magnetic powder prepared in Example 1 is replaced by the magnetic powder prepared in Examples 2-14, which correspond to Application Examples 2-14, respectively.

[0114] Application Example 15

[0115] The difference between this application example and application example 1 is that the amount of polyamide resin added is adjusted to 5 parts.

[0116] Application Example 16

[0117] The only difference between this application example and application example 1 is that the amount of polyamide resin added is adjusted to 20 parts.

[0118] Comparative Application Examples 1-6

[0119] The only difference from Application Example 1 is that the magnetic powder prepared in Example 1 is replaced by the magnetic powder prepared in Comparative Examples 1-6, which correspond to Comparative Application Examples 1-6, respectively.

[0120] Performance test: The magnets prepared in Application Examples 1-16 and Comparative Examples 1-6 were tested for resistivity at 23±2°C and relative humidity of 50-60% using a resistivity tester according to IEC60404-13-1995 standard.

[0121] The test results are shown in Table 1.

[0122] Table 1

[0123]

[0124]

[0125] analyze:

[0126] From the data results of Application Examples 1-8 and Application Examples 15-16, it can be seen that the magnetic powder provided by the present invention includes samarium iron nitrogen composite magnetic powder and ferrite composite magnetic powder, and the prepared magnet exhibits a high resistivity of up to 1.28×10 -2 When preparing the magnet, the content of polyamide resin will also affect the resistivity. When the mass ratio of polyamide resin to samarium iron nitrogen magnetic powder is in the range of (5-20):100, the magnet exhibits a high resistivity.

[0127] From the data results of Application Examples 1 and 9-10, it can be seen that when the amount of phosphoric acid added is controlled at 0.1-10 parts, that is, when the mass ratio of SmFeN magnetic powder to phosphoric acid is controlled at 100:(0.1-10), the obtained magnet has a higher resistivity. When the amount added is too low, a dense phosphating film cannot be formed, and it is difficult to improve the anti-oxidation performance of SmFeN magnetic powder; when the amount added is too high, it is unnecessary, the thickness of the phosphorus coating layer is difficult to increase, and the effects of anti-oxidation and improving resistivity are sufficient. Excessive addition will increase costs and may cause a decrease in magnetic properties, which is not worth the loss.

[0128] From the data results of Application Examples 1 and 11-12, it can be seen that when the amount of ferrite added is controlled at 1-49 parts, that is, when the mass ratio of SmFeN magnetic powder to ferrite is controlled at 100:(1-49), the obtained magnet has a higher resistivity. When the amount added is too low, the resistivity cannot be effectively improved; when the amount added is too high, the ferrite content in the magnetic powder is too high. Generally speaking, the magnetic properties of ferrite are lower than those of SmFeN. If the ferrite content is too high, the overall magnetic properties will decrease.

[0129] From the data results of Application Examples 1 and 13-14, it can be seen that when the amount of zinc oxide added is controlled at 0.1-10 parts, that is, when the mass ratio of samarium iron nitrogen magnetic powder to zinc oxide is controlled at 100: (0.1-10), the obtained magnet has a higher resistivity. When the amount added is too low, the zinc oxide cannot be effectively filled in the gaps of the magnetic powder, and the zinc oxide coating cannot be formed, resulting in a lower resistivity; when the amount added is too high, it is unnecessary, the thickness of the zinc oxide coating is difficult to increase, and the effects of anti-oxidation and increasing resistivity are sufficient. Excessive addition will increase costs and may cause a decrease in magnetic properties, which is not worth the loss.

[0130] It can be seen from the data results of Application Example 1 and Comparative Application Examples 1-4 that if the prepared magnetic powder does not contain samarium iron nitrogen composite magnetic powder, the magnetic properties of the magnetic powder and the magnet will be too low and cannot meet the use requirements; if the prepared magnetic powder does not contain ferrite composite magnetic powder, the resistivity will be too low and cannot meet the use requirements; if in the prepared magnetic powder, the surface of the samarium iron nitrogen core is only coated with a zinc oxide coating layer, and there is no phosphorus coating layer, the resistivity will be reduced; if in the prepared magnetic powder, both the samarium iron nitrogen composite magnetic powder and the ferrite composite magnetic powder do not contain a zinc oxide coating layer, the resistivity will be reduced.

[0131] It can be seen from the data results of Application Example 1 and Comparative Application Examples 5-6 that if phosphoric acid, ferrite and zinc oxide are added together for ball milling, the phosphoric acid will react with zinc oxide first and will not react with the samarium iron nitrogen magnetic powder, and the oxidation resistance will not be improved; if phosphoric acid is added first for ball milling, and then ferrite and zinc oxide are added together for ball milling, the resistivity will decrease.

[0132] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A high resistivity magnetic powder, characterized in that: The high resistivity magnetic powder includes samarium iron nitrogen composite magnetic powder and ferrite composite magnetic powder; The samarium iron nitrogen composite magnetic powder comprises a samarium iron nitrogen core, and a phosphorus coating layer and a zinc oxide coating layer sequentially arranged on the surface of the samarium iron nitrogen core from the inside to the outside; The ferrite composite magnetic powder comprises a ferrite core and a zinc oxide coating layer arranged on the surface of the ferrite core.

2. The high resistivity magnetic powder according to claim 1, characterized in that: The mass ratio of the samarium iron nitrogen composite magnetic powder to the ferrite composite magnetic powder is 100:(1-49).

3. The high resistivity magnetic powder according to claim 1 or 2, characterized in that: In the samarium iron nitrogen composite magnetic powder, the thickness of the phosphorus coating layer is 10-100 nm; Preferably, the ferrite core comprises a permanent ferrite core; Preferably, in the samarium iron nitrogen composite magnetic powder, the thickness of the zinc oxide coating layer is 50-200 nm; Preferably, in the ferrite composite magnetic powder, the thickness of the zinc oxide coating layer is 50-200 nm.

4. A method for preparing high resistivity magnetic powder according to any one of claims 1 to 3, characterized in that: The preparation method comprises: Phosphorus-containing substances, ferrite magnetic powder and zinc oxide are sequentially added to the samarium iron nitrogen magnetic powder, and ball milling is performed to obtain the high resistivity magnetic powder.

5. The preparation method according to claim 4, characterized in that: The phosphorus-containing substance includes phosphoric acid and / or phosphate; Preferably, the mass ratio of the samarium iron nitrogen magnetic powder to the phosphorus-containing substance is 100:(0.1-10); Preferably, the ferrite magnetic powder comprises permanent ferrite magnetic powder; Preferably, the mass ratio of the samarium iron nitrogen magnetic powder to the ferrite magnetic powder is 100:(1-49); Preferably, the D50 particle size of the zinc oxide is 20-100 nm; Preferably, the mass ratio of the samarium iron nitrogen magnetic powder to the zinc oxide is 100:(0.1-10).

6. The preparation method according to claim 4 or 5, characterized in that: The ball milling is a wet ball milling; Preferably, the ball milling specifically comprises: (1) adding a phosphorus-containing substance to the samarium iron nitrogen magnetic powder and performing a ball milling to obtain a primary ball milling material; (2) adding ferrite powder to the primary ball mill material, and performing secondary ball milling to obtain secondary ball mill material; (3) adding zinc oxide to the secondary ball mill material and performing a third ball milling; Preferably, before the ball milling, the samarium iron nitrogen magnetic powder is pre-ball milled; Preferably, the pre-ball milling is wet ball milling.

7. The preparation method according to claim 6, characterized in that: The rotation speeds of the pre-milling, the primary milling, the secondary milling and the tertiary milling are independently 200-1500 r / min; Preferably, the total time of the pre-ball milling, the first ball milling, the second ball milling and the third ball milling is 0.1-10h; Preferably, the pre-milling time is 0.1 to 8 hours; Preferably, the time of the first ball milling, the second ball milling and the third ball milling is independently 0.1 to 2 hours.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The preparation method further comprises: after the ball milling, sequentially performing the steps of separation and drying; Preferably, after obtaining the separated product through the separation, the separated product is mixed with a coupling agent and the drying step is performed; Preferably, the mass ratio of the samarium iron nitrogen magnetic powder to the coupling agent is 100:(0.1-5); Preferably, the drying temperature is 50-200° C., and the drying time is 1-24 h.

9. The preparation method according to any one of claims 4 to 8, characterized in that: The preparation method specifically comprises: (I) pre-milling the samarium iron nitrogen magnetic powder to obtain a pre-milled material, wherein the mass ratio of the milling balls used in the pre-milling to the samarium iron nitrogen magnetic powder is (5-10):1, and the reagent used in the pre-milling includes at least one of ethanol, isopropanol and gasoline, and the mass ratio of the reagent to the samarium iron nitrogen magnetic powder is (1-2):1; (II) adding a phosphorus-containing substance to the pre-milled material, performing a first ball milling to obtain a first ball milled material; adding ferrite magnetic powder to the first ball milled material, performing a second ball milling to obtain a second ball milled material; adding zinc oxide to the second ball milled material, performing a third ball milling to obtain a third ball milled material; (III) Separating the tertiary ball milling material, mixing the separated product with a coupling agent, and drying it at 50-200° C. for 1-24 h under vacuum or inert atmosphere to obtain the high resistivity magnetic powder.

10. A magnet, characterized in that: The magnet comprises the high resistivity magnetic powder according to any one of claims 1 to 3.